Kuwaiti women’s entry into judgeship in 2020: The long journey from law graduates in 1967 to public prosecutors in 2013, and what happened on the path towards the judiciary - Fatima Alhewail (Oñati Socio-Legal Series)
On 30 June 2020, Kuwait celebrated the appointment of eight female judges for the first time in the nation’s history. Women’s access to judgeship was preceded by the admittance of women as public prosecutors in 2013, which is the main gate to become a judge in Kuwait. As of 2020, female prosecutors constitute 27 per cent of the total number of public prosecutors in Kuwait. The article points out drivers for change in Kuwaiti society which opened up for women’s appointment as judges. It addresses the five-year period between 2013-2020 preceding the appointment of women judges, and debates that arose when eight women judges were appointed amidst the coronavirus pandemic which broke out in March 2020. Three questions are explored: First, how and why have Kuwaiti women been appointed as judges in 2020, more than five decades after women entered the field of law studies in 1967? Secondly, what forms of opposition were voiced in public through the Kuwaiti media against appointing women as judges? Thirdly, which civil society groups supported women’s entry into judgeship, and what arguments did they use to counter the arguments of the opposition?